A Double Blind Three Center Clinical Trial on the Short-Term Efficacy of 0-(β-Hydroxyethyl)-Rutosides in Patients with Post-Thrombotic Syndrome - de Jongste, A B; Jonker, J J C; Huisman, M V; ten Cate, J W; Azar, A J (Thrombosis and Haemostasis, 1989)
A multi-centre, double blind randomized clinical triatr was designed to assess the efficacy and safety of orally administered 0-(β-hydroxyethyl)-rutosides (HR) capsules in the treatment of L0L patients with post-thrombotic syndrome. Seventeen patients were excluded from the analysis for violation of the study protocol, 4l received HR capsules (I,200 mg/day) and 43 placebo.Mean follow-up scores at the 4th and 8th week show that the HR patients displayed an improved state of tiredness as compared to the placebo's. The mean circumference of the calf for the HR group decreased from 390 (± 33) mm at visit one to 382 (± 33) mm at visit three, with a mean circumference reduction of 8.7 (± 8) mm, compared to a steady placebo circumference of 387 (± 31) mm at all 3 visits with a mean circumference reduction of only 2 mm (± 9). The estimated treatment effect at week 8 was −6.7 ffiffi, 95% confidence interval (−10.3, −3.0).The mean circumference of the ankle, decreased from 243 (± 20) mm to 238 (± 20) mm at the 4th week, contrasted with a constant placebo circumference of.24l (± 22) mm at both visits. The estimated treatment effect at week 4 was-5.4 ffiffi, 95% confidence intenral (−10.2, −0.6). However, at week 8, the estimated treatment effect was only −3.4 mm; 95% corrfidence interval (−8.6, + 1.8).In conclusion, HR capsules may show an improvement in the clinical symptoms and may show a mean circumference reduction of the calf and ankle at the 8th week, in patients with postthrombotic syndrome.
Keywords: Post-thrombotic syndrome; Deep vein thrombosis; Chronic venous insufficiency; 0-(β-hydroxyethyl)-rutosides